Facile Synthesis of Three‐dimensional Hierarchical Ni3S2@CoAl‐LDHs Nanosheet Arrays and Their Efficient Hydrogen Evolution. Issue 24 (28th October 2020) - Du, Yuhang; Lu, Yufei; Zhang, Hongjian; Nie, Zhentao; Sun, Zhicheng; Han, Congying; Li, Ruizi; Zhu, Jixin
Abstract: Designing an electrocatalyst with optimized structure and performance is vital for the electrolysis of water to produce hydrogen. Herein, a three‐dimensional (3D) hierarchical composite electrode material is proposed for alkaline hydrogen evolution reaction (HER), consisting of Co−Al hydroxides (CoAl‐LDHs) nanosheets decorated with vertically aligned nickel sulfide (Ni3 S2 ) arrays (Ni3 S2 @CoAl‐LDHs/NF). The as‐obtained electrocatalyst displays a minimum overpotential of 175 mV at 10 mA cm −2 toward HER. Electrochemical impedance spectroscopy and Tafel slope further reveals outstanding kinetics in the electrolysis process. The catalytic performance of the electrode can still maintain 90 % capacity after 1000 CV cycles. The outstanding properties of the composite material benefits from its unique 3D hierarchical structure, which promote plentiful active sites and faster electronic transfer rate. This work sheds lights on the current research of noble‐metal‐free electrocatalysts and the design of overall water splitting. Abstract : Hierarchical benefits : A three‐dimensional hierarchical arrays structure assembled from nanosheets based on nickel foam was obtained by a simple soft chemical synthesis method. The composite was employed as the electrode of water splitting device to generate hydrogen and exhibited favorable hydrogen evolution efficiency, which benefits from the novel structural design and the synergistic effect of two components of Ni3 S2 and LDHs in the hydrogen evolution reaction.